2007
DOI: 10.5897/ajb2007.000-2278
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organic and inorganic fertilizer on yield and chlorophyll content of maize (Zea mays L.) and sorghum Sorghum bicolour (L.) Moench)

Abstract: The effects of amending soil with organic (poultry manure) and inorganic fertilizer on yield and chlorophyll content of maize (Zea mays L.) and sorghum (Sorghum bicolour (L.) Moench) was carried out at the Teaching and Research (T&R) Farm of the Obafemi Awolowo University, (O.A.U.) Ile-Ife, Nigeria. The experiment was a randomised complete block design (RCBD), laid out in a split-plot arrangement in the second cropping season of year 2001 and 2002. There were four sources of fertilizer for soil amendment: inor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(25 citation statements)
references
References 6 publications
2
22
0
1
Order By: Relevance
“…Organic fertilizers are natural materials of either plant or animal source, including livestock manure, green manures, crop residues, household waste, compost, and works directly as a source of plant nutrients and indirectly influences the physical, biological and chemical properties of soil [18] [19]. Microorganisms from the soil decay the organic fertilizer to make its nutrients available for utilize by plants [13] which added into the soil and have the characteristic nature of slow release of nutrients. Open Access Library Journal…”
Section: Organic Fertilizermentioning
confidence: 99%
“…Organic fertilizers are natural materials of either plant or animal source, including livestock manure, green manures, crop residues, household waste, compost, and works directly as a source of plant nutrients and indirectly influences the physical, biological and chemical properties of soil [18] [19]. Microorganisms from the soil decay the organic fertilizer to make its nutrients available for utilize by plants [13] which added into the soil and have the characteristic nature of slow release of nutrients. Open Access Library Journal…”
Section: Organic Fertilizermentioning
confidence: 99%
“…Fertilization, particularly nitrogen fertilizer [16,17], plays an extremely important role in common cultivation techniques [18,19]. Numerous studies, using experiment data on different plants, have revealed the effects of nitrogen fertilization [20].…”
Section: Introductionmentioning
confidence: 99%
“…Also, these results align with Cetin et al (2015) who reported no variability in chlorophyll content and the rate of photosynthesis in cotton after it was subjected to different fertigation treatments. Similarly, significant variability was observed in the chlorophyll content of Zea mays and Sorghum bicolour cultivated in soils amended with organic and inorganic fertilisers (Amujoyegbe et al 2007). Although outside the scope of this research, a combination of an airpump, high-frequency H 2 O 2 application, and vortex oxygenation was reported to have yielded the highest mean value of chlorophyll in Pelargonium tomentosum (Chen et al 2010;Butcher et al 2017), suggesting that oxygenation may drive photosynthesis through increased chlorophyll production.…”
Section: Discussionmentioning
confidence: 61%